Antioxidative and Analgesic Effects of Naringin through Selective Inhibition of Transient Receptor Potential Vanilloid Member 1 - Sanung Eom; Bo-Bae Lee; Shinhui Lee; Youngseo Park; Hye Duck Yeom; Tae-Hwan Kim; Seung-Hee Nam; Junho H. Lee (MDPI AG, 2021)
Transient receptor potential vanilloid member 1 (TRPV1) is activated in response to capsaicin, protons, temperature, and free reactive oxygen species (ROS) released from inflammatory molecules after exposure to harmful stimuli. The expression level of TRPV1 is elevated in the dorsal root ganglion, and its activation through capsaicin and ROS mediates neuropathic pain in mice. Its expression is high in peripheral and central nervous systems. Although pain is a response evolved for survival, many studies have been conducted to develop analgesics, but no clear results have been reported. Here, we found that naringin selectively inhibited capsaicin-stimulated inward currents in Xenopus oocytes using a two-electrode voltage clamp. The results of this study showed that naringin has an IC50 value of 33.3 μM on TRPV1. The amino acid residues D471 and N628 of TRPV1 were involved in its binding to naringin. Our study bridged the gap between the pain suppression effect of TRPV1 and the preventive effect of naringin on neuropathic pain and oxidation. Naringin had the same characteristics as a model selective antagonist, which is claimed to be ideal for the development of analgesics targeting TRPV1. Thus, this study suggests the applicability of naringin as a novel analgesic candidate through antioxidative and analgesic effects of naringin.